2021
DOI: 10.1021/acs.cgd.1c00684
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fe Deficiency and Co Substitution in Polycrystalline and Single Crystals of Fe3GeTe2

Abstract: Fe3GeTe2 is a two-dimensional van der Waals material with a ferromagnetic ground state and a maximum transition temperature T c ∼ 225 K. However, when Fe3GeTe2 is synthesized, lower values of T c are often reported. This is attributed to a deficiency in the Fe at the 2c site in the crystal structure. Here, we investigate the effect of Fe deficiency and the substitution of Co for Fe on the magnetic properties of this system. We have synthesized both polycrystalline material and single crystals by chemical vapor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 37 publications
3
19
0
Order By: Relevance
“…A clear transition point corresponding to the Curie temperature T C = 191 ± 2 K is observed, with γ = 1.3 ± 0.1, which is close to the typical exponent for a three-dimensional Ising magnet (γ ∼ 1.25) [32]. We note that the Curie temperature is significantly lower than expected for stoichiometric FGT [21,[33][34][35][36], indicating that our material is slightly Fe deficient [37,38]. Following these works, we estimate that the region used for our experiments has an Fe deficiency of less than 7% (i.e.…”
Section: Methodssupporting
confidence: 70%
“…A clear transition point corresponding to the Curie temperature T C = 191 ± 2 K is observed, with γ = 1.3 ± 0.1, which is close to the typical exponent for a three-dimensional Ising magnet (γ ∼ 1.25) [32]. We note that the Curie temperature is significantly lower than expected for stoichiometric FGT [21,[33][34][35][36], indicating that our material is slightly Fe deficient [37,38]. Following these works, we estimate that the region used for our experiments has an Fe deficiency of less than 7% (i.e.…”
Section: Methodssupporting
confidence: 70%
“…2a–d. 48,49 The unit cell of Fe 3 X ( X =Ge and Ga)Te 2 consists of one Fe 3 X ( X =Ge and Ga) layer and two adjacent Te layers, in which the Fe 3 X layer refer to Fe 2+ Ge 4− sandwiched by Fe 3+ atoms and the Ge and Fe 2 bonds covalently in Fe 3 GeTe 2 . 50 Different from those of Fe 3 GeTe 2 , the Fe valence states of Fe 3 GaTe 2 are Fe 0 and Fe 3+ were confirmed by X-ray photoelectron spectroscopy.…”
Section: Fundamentals Of Fe3x(x=ge and Ga)te2mentioning
confidence: 99%
“…54 Mayoh et al also found the dependence of lattice constant on Fe concentrations and further revealed that both a and c decrease when Fe atoms are replaced by Co atoms in Fe 3− y Co y GeTe 2 . 49…”
Section: Fundamentals Of Fe3x(x=ge and Ga)te2mentioning
confidence: 99%
See 2 more Smart Citations